Simulating Mn02 nanoparticles using simulated amorphisation and recrystallisation - Sayle, Thi X. T.; Catlow, C. Richard A.; Maphanga, R. Regina; Ngoepe, Phuti E.; Sayle, Dean C. (American Chemical Society, 2011)
Models of MnO2 nanoparticles, with full atomistic detail, have been generated using a simulated amorphization and recrystallization strategy. In particular, a 25,000-atom “cube” of MnO2 was amorphized (tension-induced) under molecular dynamics (MD). Long-duration MD, applied to this system, results in the sudden evolution of a small crystalline region of pyrolusite-structured MnO2, which acts as a nucleating “seed” and facilitates the recrystallization of all the surrounding (amorphous) MnO2. The resulting MnO2 nanoparticle is about 8 nm in diameter, conforms to the pyrolusite structure (isostructural with rutile TiO2, comprising 1 × 1 octahedra) is heavily twinned and comprises a wealth of isolated and clustered point defects such as cation vacancies. In addition, we suggest the presence of ramsdellite (2 × 1 octahedra) intergrowths. Molecular graphical snapshots of the crystallization process are presented.